Impaired Neutrophil Chemotaxis in Chronic Obstructive Pulmonary Disease - Yoshikawa, Takahiro; Dent, Gordon; Ward, Jon; Angco, Gilbert; Nong, Guangmin; Nomura, Naho; Hirata, Kazuto; Djukanovic, Ratko (American Journal of Respiratory and Critical Care Medicine, 2007)
Neutrophilic airway inflammation is considered to be a major factor in the pathogenesis of chronic obstructive pulmonary disease (COPD), with sputum and bronchoalveolar lavage neutrophil counts broadly correlating with disease severity. The mechanisms responsible for neutrophil accumulation are poorly understood, but they could involve increased influx and/or survival of these cells. To investigate whether neutrophil chemotactic responsiveness and/or chemotactic activity in airway secretions are increased in subjects with COPD. Chemotaxis experiments were performed using induced sputum supernatants from subjects with and without COPD as a source of chemotactic activity, and neutrophils from healthy donors as responder cells. In addition, chemotactic responses to N-formyl-Met-Leu-Phe (fMLP) and interleukin-8 (IL-8/CXCL8) were studied using neutrophils from healthy subjects and subjects with COPD. As reported in the literature, sputum neutrophil counts were significantly increased in subjects with COPD compared with healthy subjects. However, this was associated with reduced chemotactic activity in sputum in COPD, as judged by reduced chemotaxis to the fluid phase of sputum from subjects with COPD compared with healthy subjects. Furthermore, whereas neutrophils from subjects with stage I COPD had normal responses to fMLP and IL-8, subjects with more severe stage II-IV COPD showed reduced levels of spontaneous migration and chemotaxis to fMLP and IL-8. Neither increased chemotactic activity in the airways nor increased chemotactic responsiveness of neutrophils explains the increased number of these cells in subjects with stable COPD. The implications of the observed reduction in neutrophil chemotactic activity remain to be established.